Attitudes towards primary care career in community health centers among medical students in China. Issue 1 (December 2016) - Zhang, Lingling; Bossert, Thomas; Mahal, Ajay; Hu, Guoqing; Guo, Qing; Liu, Yuanli
Abstract Background Very few of the primary care doctors currently working in China's community health centers have a college degree (issued by 5-year medical schools). How to attract college graduates to community services in the future, therefore, has major policy relevance in the government's ongoing efforts to reform community health care and fill in the long-absent role of general physicians in China. This paper examined medical school students' attitudes towards working in communities and the factors that may affect their career choices in primary care to inform policy on this subject. Methods A cross-sectional survey was designed upon the issuance of community health reform policy in 2006 by the Chinese government. The survey was conducted among 2714 medical students from three medical schools in representative regions in China. Binomial and multinomial regression analyses were carried out using a collection of plausible predictors such as place of rearing, income, etc. to assess their willingness to work in communities. Results Of the 2402 valid responses, besides 5.7 % objection to working in communities, 19.1 % expressed definite willingness. However, the majority (41.5 %) of students only consider community job as a temporary transition, in addition to 33.7 % using it as their backup option. The survey analyses found that medical students who are more likely to be willing to work in communities tend to come from rural backgrounds, have more exposure to community health reform, and possess certain personally held value and fit. Conclusion To attract more graduates from 5-year medical schools to work in communities, a targeted recruiting approach or admission policy stands a better chance of success. The findings on the influencing factors of medical students' career choice can help inform policymakers, medical educators, and community health managers to improve the willingness of swing students to enter primary care to strengthen basic health services.